Photothermal Therapeutic Gold Nanoparticles Loaded with PD-L1 siRNA Enhanced Killing of NSCLC Cells by Immune Cells - Gao L; Yang LH; Jiang FC; Ye WY; Chen X; Liu ZJ; He RQ; Huang WY; Feng ZB; Kong JL; Lai ZF; Chen G (International Journal of Nanomedicine, 2025)
Li Gao,1,* Li-Hua Yang,2,* Fang-Cheng Jiang,1,3 Wang-Yang Ye,4 Xin Chen,3 Zhao-Ji Liu,3 Rong-Quan He,2 Wan-Ying Huang,1 Zhen-Bo Feng,1 Jin-Liang Kong,5 Ze-Feng Lai,3,6 Gang Chen1 1Department of Pathology, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People’s Republic of China; 2Department of Medical Oncology, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People’s Republic of China; 3Guangxi Key Laboratory of Pharmaceutical Precision Detection and Screening, Pharmaceutical College, Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People’s Republic of China; 4College of Basic Medicine, Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People’s Republic of China; 5Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital of Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People’s Republic of China; 6State Key Laboratory of Targeting Oncology, Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Gang Chen, Email chengang@gxmu.edu.cn Ze-Feng Lai, Email laizefeng@gxmu.edu.cnBackground: Although immune checkpoint blocking (ICB) therapeutic agents have significantly improved the survival for many cancer patients, the efficacy of ICB therapy for non-small cell lung cancer (NSCLC) patients remains limited. Combining ICB therapy with other strategies that is able to stimulate tumor immunogenicity or increase infiltration of T cells aroused great concern in cancer therapy.Results: Herein, we constructed a kind of AuNP@NH2-PEG-SH/PD-L1 siRNA nanoparticle complex which showed prominent photothermal therapeutic (PTT) effects triggered by NIR laser and could efficiently deliver PD-L1 siRNA into NSCLC cells (knock-down efficiency were 75.8% and 83% in HCC827 and A549 cells). During the process of photothermal stimulation, discrepancies in heat shock protein expression were observed in NSCLC cells. Knocking down PD-L1 expression in NSCLC cells such as A549 and HCC827 cells activated the co-culturing Jurkat cells and enhanced their tumor-killing effect in vitro (cell inhibition rate was 62.65% for HCC827 cells and 57.03% for A549 cells). The gold nanoparticle complexes exhibited remarkable PTT effect for the engrafted NSCLC cells in zebrafish larvas. Furthermore, the nano complexes could promote the activation of the xenografted human peripheral blood mononuclear cells (PBMCs) and enhance the killing of the NSCLC cells in the larvas.Conclusion: It is well known that gold nanoparticle is one of the several metal nanoparticles approved for clinical trial by American FDA. This work has demonstrated the outstanding PTT and immunotherapeutic effects of gold nanoparticle complexes on NSCLC, indicating great potential in clinical regiment of lung cancers.Keywords: non-small cell lung cancer, AuNP, photothermal therapy, antitumor immunity, PD-L1